VLSI implementation of cellular automata: Modulo-arithmetic units - Srisuchinwong, Banlue; Thanailakis, Antonios; Hicks, Peter J.; York, Trevor A.; Tsalides, Ph. (Zielona Góra: Uniwersytet Zielonogórski)
Cellular Automata (CA) and their natural affinity for VLSI are discussed. Group behaviour of CA is related to that for modulo-arithmetic units and this leads to an architecture for modulo multiplication. Implementation of a mod-127 multiplier using two techniques, full custom CMOS design and Xilinx programmable gate arrays is described. The principle of operation is based on two identical 12x12, null-bounded, CA each having semi-group order 126.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka